Regional Native Income (Pad) Towards Regional Development In Tegal Regency - Ummu Najwa; Hendri Hermawan Adinugraha (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Timor, 2022)
This research is based on the decline in the growth of Regional Original Income (PAD) in the 2017 and 2021 Fiscal Years. As a source of regional financing, PAD revenue should continue to increase. The purpose of this study was to determine the level of efficiency, effectiveness and contribution of local taxes in increasing local revenue in Tegal Regency in 2017-2021. This study uses descriptive quantitative analysis techniques. The source of data used in this study is secondary data, namely data obtained indirectly through intermediary media such as other people or archive documents of the Regional Revenue Service (Dispenda) of Tegal Regency. The data used is a report on the realization of Tegal Regency's regional income for the 2017-2021 fiscal year. The average regional tax efficiency of Tegal Regency in 2017-2021 is 84% classified in the criteria of being quite efficient. The average level of effectiveness of the Tegal Regency regional tax in 2017-2021, which is 96.05%, is classified in the Ineffective criteria. The average regional tax contribution rate of Tegal Regency in 2017-2021, which is 454%, is classified as very good.